(untitled) (Economics and region, 2017)
UDC: 330.322.2 (477.53) Voloshyna, Assistance Lecturer. Ya. Hnatenko, Lecturer. O. Havrylenko. Poltava National Technical Yuri Kondratyuk University. State and Prospects of Investment in Poltava region. The features of investment activities in Poltava region are explored. The structure of capital investment in Ukraine and its share in Poltava region are evaluated. The main sources of investment are covered. Investment income in industries of national economy is analyzed. The prospects of investing in Poltava region are outlined. Keywords: investment, capital investment, sources of investment, investment activities.